Clinical characteristics of patients with myositis and autoantibodies to different fragments of the Mi-2β antigen. Issue 2 (12th January 2006) - Hengstman, G J D; Vree Egberts, W T M; Seelig, H P; Lundberg, I E; Moutsopoulos, H M; Doria, A; Mosca, M; Vencovsky, J; van Venrooij, W J; van Engelen, B G M
Abstract : Objectives: To assess the clinical implications of autoantibodies directed against different parts of the Mi-2β autoantigen in patients with myositis. Methods: A systematic assessment of the clinical, laboratory, and histological characteristics of 48 anti-Mi-2 positive patients from six European centres was made. Anti-Mi-2 autoantibodies were determined with an ELISA using four overlapping fragments spanning the entire amino acid sequence of the autoantigen. Data were compared with results for a large group of anti-Mi-2 negative patients with myositis published previously. Results: Anti-Mi-2 autoantibodies were found in dermatomyositis, polymyositis, and inclusion body myositis. In general, myositis with anti-Mi-2 autoantibodies was characterised by relatively mild disease, sometimes accompanied by extramuscular symptoms, including arthralgia, arthritis, Raynaud's phenomenon, and interstitial lung disease. Cardiac disease was not seen, and treatment response was fair. No differences were found between patients with autoantibodies to different fragments of the Mi-2β antigen, except for a potentially increased risk of cancer in patients with antibodies directed to the N-terminal fragment of the autoantigen. Conclusions: Anti-Mi-2 autoantibodies are not a marker of a specific subtype of myositis. No significant differences between patients with autoantibodies to different fragments of the Mi-2β autoantigen are found, with the possible exception of an increased risk of cancer in patients with antibodies to the N-terminal fragment.